Five new species of Caliscelidae (Insecta, Hemiptera) from Mexico and Panama, with additional redescriptions of little-known species - de Freitas, Abner S.; Dietrich, Christopher H.; Takiya, Daniela M. (European Journal of Taxonomy, 2020)
Five new species of Peltonotellini (Caliscelinae) are described and illustrated: Bruchomorpha pseudodorsata sp. nov., Fitchiella brachyrhina sp. nov., Protrocha nigrilutea sp. nov. and P. punctatosa sp. nov. from Mexico, and Fitchiella zahniseri sp. nov. from Panama. Additionally, five previously described species are redescribed based on newly collected specimens: Aphelonema brevata Caldwell, 1945 (proposed original combination), Bruchomorpha decorata Metcalf, 1923, Bruchomorpha mormo Kirkaldy, 1907, Nenema virgata (Doering, 1941) and Protrocha nesolitaria (Caldwell, 1945). Bruchomorpha decorata is recorded from Panama for the first time. Redescriptions provide new information on the distribution of sensory pits and the first detailed descriptions of male and female terminalia for these species.